DEVELOPMENT THE STUDY OF EFFECTIVENESS COOPERATIVE LEARNING MODEL IN CLASSROOM - Astuti, Sariyah (JLCEdu (Journal of Learning and Character Education), 2021)
This research focused on the use of the Think Pair Share technique in Students’ Writing Descriptive Text and the character development effectiveness of using the cooperative learning model in the classroom. This learning model is a kind of Development cooperative learning model to encourage students actively involved in the learning process. This research was conducted with qualitative design type library research. The instrument of this research was six articles that related to Think Pair Share for students writing skills in Descriptive text, books, and journals. The qualitative data were analyzed by data reduction, data display, and verification. The result of the research based on the implementation of each article showed that Think Pair Share was effective to helped students in writing descriptive text. It showed from the character development of effectiveness aspect that suitable to the article, such as quality of learning is marked by the success of the students to achieve the lesson goals. The appropriate level of instruction showed the ability of the teacher to ensure the readiness of each student to learn. Incentives showed the ability of the teacher to encourage students to be motivated to learn. Times setting, shown from the steps of the lesson process used.